2020
DOI: 10.1111/nyas.14410
|View full text |Cite
|
Sign up to set email alerts
|

Evolution is a double‐edged sword, not a silver bullet, to confront global change

Abstract: Although there is considerable optimism surrounding adaptive evolutionary responses to global change, relatively little attention has been paid to maladaptation in this context. In this review, we consider how global change might lead populations to become maladapted. We further consider how populations can evolve to new optima, fail to evolve and therefore remain maladapted, or become further maladapted through trait‐driven or eco–evo‐driven mechanisms after being displaced from their fitness optima. Our goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 115 publications
(230 reference statements)
1
21
0
Order By: Relevance
“…Indeed, the presence of unequal trade‐offs suggests that the urban acorn ant populations are still somewhat maladapted (not yet on a fitness peak) to the many, rapid stressors imposed by cities, even if they are currently exhibiting adaptive evolutionary responses to urbanization. Thus, although it is encouraging that contemporary urban local adaptation is possible, unfortunately, the results of our study join a broad range of evidence showing that the magnitude and rate of anthropogenic environmental change could exceed the capacity of some species to keep pace (reviewed in Diamond and Martin 2020a; and see Radchuk et al. 2019).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, the presence of unequal trade‐offs suggests that the urban acorn ant populations are still somewhat maladapted (not yet on a fitness peak) to the many, rapid stressors imposed by cities, even if they are currently exhibiting adaptive evolutionary responses to urbanization. Thus, although it is encouraging that contemporary urban local adaptation is possible, unfortunately, the results of our study join a broad range of evidence showing that the magnitude and rate of anthropogenic environmental change could exceed the capacity of some species to keep pace (reviewed in Diamond and Martin 2020a; and see Radchuk et al. 2019).…”
Section: Discussionsupporting
confidence: 55%
“…Cities provide an unplanned, experimental arena for better understanding the process of local adaptation (or their lack thereof) to novel and changing environments (Diamond and Martin 2020a). Although it is now clear that rapid evolutionary responses, taking place within the timescale of human lifespans, routinely occur in natural populations (Hendry and Kinnison 1999; Reznick et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the bright side, some thermal selection experiments have demonstrated that heat tolerance can evolve, when directly selected upon (Bubliy and Loeschcke 2005;Hangartner and Hoffmann 2016), although the ecologically relevance of such selection protocols might be questioned. Using the terminology of Diamond and Martin (2020), the question stands: can thermal adaptation be regarded as the silver bullet to fight global warming? According to our experimental data, the quick answer is no, not in the short run at least.…”
Section: Discussionmentioning
confidence: 99%
“…Why then should acorn ants evolve a higher metabolic rate in warmer urban environments? Although there has been much focus in the literature on the possibility of evolutionary rescue from the impacts of environmental change, including global climate change and urbanization (Carlson, Cunningham, & Westley, 2014), recent work has highlighted the importance of maladaptive responses (Brady et al., 2019; Diamond & Martin, 2020). Most benignly, maladaptive responses could refer to simply not being able to keep pace with the magnitude and rate of environmental change (Radchuk et al., 2019); however, maladaptive responses can also manifest as responses in the opposite direction to cope with environmental change (Dayananda & Webb, 2017; Hale, Morrongiello, & Swearer, 2016; Van Dyck, Bonte, Puls, Gotthard, & Maes, 2015).…”
Section: Discussionmentioning
confidence: 99%